Analisis Efektivitas Kampanye Pengurangan Penggunaan Plastik:Tinjauan Literatur Sistematis terhadap Strategi dan Dampaknya - Tri Kurniawati; Yunia Wardi; Susi Evanita (Universitas Negeri Padang, 2025)
This article presents a systematic literature review of plastic reduction campaigns in Indonesia, analyzing their strategies and impact across various sectors including government, civil society, private industry, and educational institutions. The study employs the PRISMA protocol and bibliometric analysis using Vosviewer for mapping the current research and identify effective communication approaches. Findings indicate that integrated campaigns—combining policy enforcement, public education, digital engagement, and participatory programs—are most effective in influencing behavior change. A case study conducted among students of the Faculty of Economics and Business at Universitas Negeri Padang reveals a significant gap between awareness and active participation, with only a small percentage of students fully engaged in anti-plastic initiatives. The study concludes that localized, behavior-based strategies supported by institutional policy and educational integration are essential to increase engagement and foster sustainable habits. This research contributes to the development of more adaptive and evidence-based communication models for addressing plastic pollution in Indonesia.